A educação financeira e suas contribuições no planejamento familiar dos alunos da escola estadual de ensino fundamental Antônio Brasil. - SILVA, Lidia do Espirito Santo da (2023)
The research carried out proposed an analysis of financial education and its contributions to family planning for students at the Antônio Brasil State High School in Tomé-Açu/Pá. Since the research problem sought to know what are the influentes of financial education and its contributions on family planning of high school students at Escola Estadual Antônio Brasil? The research was developed at Antônio Brasil State High School, located at Rua Francisco Soares, No. 311, Bairro Campina in the city of Tomé Açu, where the research was motivated by the need to know the applicability of mathematics in relation to financial education developed in the classroom. and the influences on family planning of high school students. The general objective of the research sought to analyze financial education and its consequences within the family planning of high school students at Escola Estadual Antônio Brasil and the specific seeks to identify the main mathematical knowledge applied to financial education in the classroom by teachers, describe the main novelties are skills acquired by students after having contact with financial education and evaluating the consequences of mathematical knowledge on students' family planning. The research rationale was based on the authors Silveira (2019), Martins (2004), and Sampieri (2013). In this research, the descriptive non-experimental design was used as a methodology, within a quantitative approach. The study population is composed of 20 (twenty) teachers of these 5 mathematics and 500 (five hundred) students. The research analyzed the financial education related to mathematical knowledge and its consequences on the family planning of students from Antônio Brasil state school.